The style design of professional female vest based on kansei engineering. Issue 1 (28th August 2019) - Chen, Daoling; Cheng, Pengpeng
Abstract : Purpose: The purpose of this paper is to study the style design methods of professional female vests that meet the emotional needs of consumers. Design/methodology/approach: Using the theory of kansei engineering as a guide to screen representative samples of female professional vests and relevant emotional vocabularies of styles, through morphological analysis, style design elements of female professional vests are extracted, the fifth-order semantic difference questionnaire was used to establish the perceptual assessment matrix for design elements, the correlation analysis method and multiple linear regression analysis were used to analyze the results of the perceptual evaluation of the sample, find out the relationship between the perceptual vocabulary and design elements of professional female vest styles, and establish a regression model, finally, it is verified by random samples of the market, so as to guide the development of new products. Findings: The seven design elements extracted from professional female vest styles have an impact on consumer perception, by using a linear analysis method, the correspondence between perceptual perception of consumers and style design elements can be quantified and a model can be established to accurately predict consumers' perceptual intentions. Originality/value: The application of perceptual engineering in the style design of professional female vests provides a new idea for the design of clothing styles. It helps garment companies and designers to determine the development direction of professional woman's vest styles, while the research results provide design reference for other products.